Early Urbanism in Europe : The Trypillia Megasites of the Ukrainian Forest-Steppe - Gajdarska, Biserka (2020)
For over 60 years, the accepted view of cultural evolution was that the world's first cities developed in the Fertile Crescent in the 4th millennium BC. This view overlooks the emergence of a much neglected class of sites-the Trypillia megasites of the Ukrainian forest-steppe. The megasites were in fact larger and earlier than the Mesopotamian cities and demonstrate an alternative pathway towards cities without strong central administration and any later urban legacy. In this book, a team of international authors examines the hypothesis of independent Eastern European urbanism using the evidence gathered from the multi-disciplinary investigation of the megasite of Nebelivka.